Frequency of Stafne's bone cavity. A retrospective analysis in panoramic radiographs - Juan Angel Paucar Estrella; Dante Angeles Romero; Sandro Alexander Lévano Loayza; Ana Paola Trevejo Bocanegra (Editorial Ciencias Médicas, 2023)
Introduction: Stafne's bone cavity is a rare, radiolucent, well-demarcated anatomic variant that usually occurs in the molar region near the mandibular angle and below the canal for the inferior dental nerve. It is frequently misdiagnosed with other pathological entities. Objective: To determine the frequency of Stafne's bone cavity in panoramic radiographs of the Oral and Maxillofacial Radiology Service of the Teaching Dental Care Center "Cayetano Heredia", from 2015 to 2019. Methods: An observational, descriptive, cross-sectional and retrospective study was performed on a sample of 17875 panoramic radiographs. Demographic variables such as gender, age, location and shape were considered; subsequently tables of contents were performed for data analysis. Results: Among the 17875 patients, only 24 (0.13 %) had Stafne's bone cavity, including 16 males and 8 females. The eighth decade of life presented the highest number of cases with 6 (0.4 %). The right posterior location accounted for 13 (54.17 %), the left posterior with 7 (29.17 %) and the anterior with 4 (16.67 %). The oval shape with 23 (95.83 %) and round with only 1 (4.17 %). Conclusions: The frequency of Stafne's bone cavity was 0.13 % with male sex predilection, eighth decade of life, right posterior location and oval shape.